LANGUAGE ERROR ANALYSIS ON OFFICIAL LETTERS DESA KALILOKA’S KECAMATAN SIRAMPOG KABUPATEN BREBES (ANALISIS KESALAHAN BERBAHASA PADA SURAT DINAS DESA KALILOKA KECAMATAN SIRAMPOG KABUPATEN BREBES) (Jurnal Gramatika, 2019)
The purposes of this research are : (1) to describes the Indonesia language eror forms on official letters; and (2) the determinant factors of language error forms on official letters of Desa Kaliloka’s, Kecamatan Sirampog, Kabupaten Brebes. This research is a qualitative descriptive research. The result of this research are as follows. First, the Indonesian language error forms found on the official letters of Desa Kaliloka’s such as: errors in the field of spellings, morphologies, and syntaxes. Second, the determinant factors of Indonesian language error forms on official letters Desa Kaliloka’s are: a) writing official letters only refers to the village had and sampel letters from the subdistrict; b) the official letter writers more than one person; c) no training about official letter from the local government; and d) ignorance of the existance of KBBI and PUEBI which are the basic guidelines of language.